An Analysis of Figurative Language in Poems by Laksmi Pamuntjak - Marce Laimena; Stella Rose Que (MATAI: International Journal of Language Education, 2022)
Figurative language is used to beautify literary work, especially poems. It can make the poems more exciting and unique. But some readers cannot identify the figurative language used in poetry. The poem's readers will read, analyze, and interpret poetry without considering the use of figurative language. The research objectives were to explain the kinds of figurative language used in selected poems by Laksmi Pamuntjak and the use of figurative language in Laksmi Pamuntjak's poems. This is qualitative research with content analysis. This approach offered to analyze data by choosing some poems by Laksmi Pamuntjak, reading the poems, identifying the figurative language used in the poems, then analyzing the figurative language used in the poems. In analyzing figurative language in Laksmi Pamuntjak's poems, the researcher grouped them based on the figurative language used in each poem. In analyzing data, the researcher analyzed every figurative language found in the poems and the last drawing conclusion based on the result of the data analysis. This research revealed figurative language in every selected poem by Laksmi Pamuntjak. The figurative languages used in the poems vary. Each poem had characteristics, so the use of figurative language was also diverse. This research will give readers advantages, especially the lectures and the college students. There is hope that more research will analyze figurative language in poetry and other literary works.